A dimensão técnico-pedagógica do apoio matricial no Núcleo de apoio à saúde da família (NASF) em Belo Horizonte - Thayna Larissa Aguilar dos Santos (2019)
The Family Health Support Centers (NASF) has as an organizer of its work the matrix support, which is divided into two dimensions, one assistance and another technical-pedagogical. We are interested in the technical-pedagogical dimension of the matrix support performed by the NASF, for their potential to contribute to a greater autonomy production in the Family Health Teams (EqSF) and to qualify their actions in health. However, the priorization of care in the NASF, in detriment of its technical-pedagogical aspect, is one of their great challenges, according to the literature of the theme. The objective of this study was to analyze the technicalpedagogical dimension of the matrix support in the NASF from Belo Horizonte (BH) and as specific objectives: to know how the technical-pedagogical dimension is presented in the conceptions and expectations of EqSF and NASF professionals about NASF matrix support; understand how the sharing of knowledge and accountability for NASF and EqSF cases occurs; to understand potentialities and possible difficulties in the execution of the technicalpedagogical practices within NASF ambit. For this, participant observations were made, interviews with BH NASF technical coordinators, and reflection groups with EqSF and NASF professionals. It is a participatory research intervention-research for which an expanded collective of researchers from the university and the service was constituted, who participated in the conception of this research, decisions regarding the field, data analysis and procedural refunds. The interviews were used as reference material for the research, the data of the observation were analyzed in a deductive way from theoretical categories of the literature and the data produced in the reflection groups were analyzed in the inductive way. In the remarks of the matrix meetings, a very different reality was found between the teams. There were meetings in which was sharing of knowledge among all the professionals involved, but in some places, it was noticed difficulty in participation from some categories. Regarding accountability, in some places professionals seemed more appropriate and resolute in relation to cases, acting in an integrated way, but in other there was only the transfer of responsibility from one to another. In the reflection groups, it was considered that the matrix support falls short of what could be, often summarizing the matricity dominated by “case passing”. We verified that the professionals do not readily recognize the technical-pedagogical dimension of the matrix support, but that it is present in the practices, even though it is deprived by the ignorance of its function by the professionals; the lack of investment in the training of supporters; by demand management problems; by cross-management of UBS; by the dominance of the practice of nonshared individual care and by possible difficulties of participation of some categories, especially the community health agents.